Software that makes software better. (Economist, 2008)
The article discusses the development of software intended to improve the software development process, such as by analyzing source code for bugs, or by quantifying code quality, programmer productivity, and the cost-effectiveness of bug fixes. Experts from IBM's Rational Software unit, Microsoft Research, and Software Productivity Research are quoted.